A Study of Emotional Intelligence and Quality of Work Life Effects on Work Performance in TCS Nagpur - Thosare, Hemlata Prakash; Tekade, Atul (Journal of Neonatal Surgery, 2025)
Emotional Intelligence (EI) and Quality of Work Life (QWL) have become pivotal elements influencing employee performance in modern organizations. This study delves into the effects of EI and QWL on work performance at Tata Consultancy Services (TCS) in Nagpur. The research aims to explore the relationship between emotional intelligence, the quality of work life, and the overall work performance of employees in a corporate setting. A mixed-method approach was employed, combining both qualitative and quantitative data collection techniques through surveys and interviews with employees at TCS. The findings suggest that employees with higher emotional intelligence demonstrate better coping strategies, effective communication, and enhanced problem-solving skills, which contribute to improved work performance. Furthermore, the study identifies that a high-quality work life, characterized by job satisfaction, work-life balance, and supportive work conditions, significantly enhances the motivation and productivity of employees. The results indicate a synergistic effect, where both EI and QWL contribute to a better work environment, fostering higher job performance. This research underscores the importance of integrating emotional intelligence development programs and improving work life conditions to elevate employee engagement, satisfaction, and productivity in TCS. s valuable insights for organizations aiming to improve employee efficiency and foster a conducive work environment.